A serum-free culture medium production system by co-culture combining growth factor-secreting cells and l-lactate-assimilating cyanobacteria for sustainable cultured meat production - Chu, Shanga; Haraguchi, Yuji; Asahi, Toru; Kato, Yuichi; Kondo, Akihiko; Hasunuma, Tomohisa; Shimizu, Tatsuya (Scientific reports, 2024)
Large-scale production of cultured meat requires bulk culture medium containing growth-promoting proteins from animal serum. However, animal serum for mammalian cell culture is associated with high costs, ethical concerns, and contamination risks. Owing to its growth factor content, conditioned medium from rat liver epithelial RL34 cells can replace animal serum for myoblast proliferation. More seeded cells and longer culture periods are thought to yield higher growth factor levels, resulting in more effective muscle cell proliferation. However, RL34 cells can deplete nutrients and release harmful metabolites into the culture medium over time, potentially causing growth inhibition and apoptosis. This issue highlights the need for waste clearance during condition medium production. To address this issue, we introduced a lactate permease gene ( lldP ) and an l -lactate-to-pyruvate conversion enzyme gene ( lldD ) to generate a recombinant l -lactate-assimilating cyanobacterium Synechococcus sp. KC0110 strain. Transwell co-culture of this strain with RL34 cells exhibited a marked reduction in the levels of harmful metabolites, lactate and ammonium, while maintaining higher concentrations of glucose, pyruvate, and pyruvate-derived amino acids than those seen with RL34 cell monocultures. The co-culture medium supported myoblast proliferation without medium dilution or additional nutrients, which was attributed to the waste clearance and nutrient replenishment effects of the KC0110 strain. This culture system holds potential for the production of low-cost, and animal-free cultured meat.